Koperasi dan BMT: Urgensi Sumber Dana Usaha Mikro dalam Mencapai Kemaslahatan Masyarakat - Indah, Nur (ARZUSIN, 2023)
Funding collection and distribution institutions are the pillars of financing for micro-entrepreneurs through cooperatives and BMT institutions as a source of funds for people who need business development without high interest and easy requirements. As time goes by, the large market share of Muslims means the values that are planted in the Cooperative System and BMT are the same as the ethics of the Islamic Economic System. The ethics of Islam is mainly based on the Qur'an and Sunnah as the main sources of Islamic jurisprudence, supplemented by Ijma' qiyas and followed by other secondary sources. However, in its implementation, there are two functions of micro-finance institutions with their respective principles between cooperatives and BMTs. For this reason, it is necessary to study the respective tupoksi of cooperative institutions and BMTs so that they are able to run on their respective rails in realizing the main functions between institutions. This research is library research, using an approach to the interpretation of the Qur'an with the Maudhu' (thematic) method. Reviewing written sources such as scientific journals, reference books, literature, encyclopedias, scientific articles, scientific works, and other sources that are relevant and related to the object under study. The important role of each institution is to spearhead the development and strengthening of the economy in Indonesia by creating job opportunities and developing community MSMEs.